Population dynamics of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) at Kelavarappalli Reservoir in Tamil Nadu - Khan, M. Feroz; Panikkar, Preetha; Das, B. K. (Journal of the Inland Fisheries Society of India, 2021)
Nile tilapia, Oreochromis niloticus, is one of the most established among the introduced fishes in inland waters of India. The population characteristics of O. niloticus from Kelavarappalli Reservoir, a small reservoir of Tamil Nadu, were studied. The von Bertalanffy growth parameters (VBGF) were estimated using ELEFAN. The Lâˆžvalues were 38.7 cm and 37.6 cm for males and females, respectively. The growth coefficient K was estimated at 0.65 (males) and 0.73 (females). The fishes showed isometric growth. The fishing mortality (F) was 2.4 yr-1, the natural mortality rate (M) was 1.2 yr-1 and the total instantaneous mortality rate (Z) was estimated at 3.6 yr-1. The probability of capture of O. niloticus was 25% at 12.2 cm, 50% at 12.7 cm and 75% at 16.9 cm size range. The relative yield-per-recruit (Y'/ R) and biomass-per-recruit (B'/ R) were derived from the growth parameters and the values were 0.33 and 1.88 respectively. The expected yield at various levels of fishing mortality shows that yield increased with increased fishing suggesting that it can be increased by enhancing the effort up to an exploitation rate (E) value of 0.56. The present exploitation rate (E= 0.67) is beyond MSY and therefore the catch is declining. To sustain the tilapia fishery at Kelavarapalli the exploitation rate should be brought down to 0.56 from the present 0.67. The biomass per recruit against exploitation ratio reveals that half the stock is reduced at an exploitation ratio of 0.31. Further expansion of fishing here will be detrimental to the stock of tilapia as it suffers from both growth overfishing and recruitment overfishing. Key words Growth; Instantaneous mortality; Exploitation rate; Relative yield per recruit